The nutritive value of sainfoin (Onobrychis viciifolia), sheeps' burnet (Sanguisorba minor) and lucerne (Medicago sativa) - Meissner, H.H. (University of Pretoria, 2013)
Dissertation (MSc)--University of Pretoria, 2008.